2010
DOI: 10.1016/j.gca.2009.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Sorptive stabilization of organic matter by amorphous Al hydroxide

Abstract: Sorptive stabilization of organic matter by amorphous Al hydroxideSchneider, M.P.W.; Scheel, Th.; Mikutta, R.; van Hees, P.; Kaiser, K.; Kalbitz, K. General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you believe that digital publication of certai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
82
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(89 citation statements)
references
References 42 publications
6
82
1
Order By: Relevance
“…As previously discussed, Al-humus complexes are assumed to protect soil humus from decomposition by microorganisms and enzymes (Baldock and Broos, 2011;Mikutta et al, 2007;Schneider et al, 2010). However, Takahashi et al (2006a) showed a remarkable decrease of Al p values (7 -52%) following liming of A horizon soils from non-allophanic Andosols in a laboratory study.…”
Section: Organic Carbon Accumulation In Andosolsmentioning
confidence: 93%
“…As previously discussed, Al-humus complexes are assumed to protect soil humus from decomposition by microorganisms and enzymes (Baldock and Broos, 2011;Mikutta et al, 2007;Schneider et al, 2010). However, Takahashi et al (2006a) showed a remarkable decrease of Al p values (7 -52%) following liming of A horizon soils from non-allophanic Andosols in a laboratory study.…”
Section: Organic Carbon Accumulation In Andosolsmentioning
confidence: 93%
“…Fig. 16 directly compares the adsorption of EPS-C to Al(OH) 3(am) with that of OM-C derived from less and well humified organic soil layers (Schneider et al, 2010). The data suggest that EPS from B. subtilis exhibit a similar sorption affinity Molar Al:C = 0.53 Fig.…”
Section: Eps Adsorption Versus Coprecipitationmentioning
confidence: 96%
“…3(am) at different initial molar Al:C ratios. Data for natural OM were taken from Schneider et al (2010). The pH in each experiment was 4.5.…”
Section: Preferential Adsorption and Coprecipitation Of Eps Componentsmentioning
confidence: 99%
“…Forest soils contain up to 45 % of carbon (C) stored on land surfaces (Malmsheimer et al 2011) forming an important part of the global C budget (Schlesinger 1997;Hedges et al 2000). Climate change is expected to have significant consequences on forest soils IPCC 2013) and better models are needed to predict current and future soil carbon stocks to help guide in mitigating potential effects that are likely to be associated with climate change.…”
Section: Introductionmentioning
confidence: 99%